Heparin and penicillamine-hypotaurine-epinephrine (PHE) solution during bovine in vitro fertilization procedures impair the quality of spermatozoa but improve normal oocyte fecundation and early embryonic development - Gonçalves, F. S. [UNESP]; Barretto, L. S S [UNESP]; Arruda, R. P.; Perri, Silvia Helena Venturoli [UNESP]; Mingoti, Gisele Zoccal [UNESP] (Springer Nature, 2013)
The presence of heparin and a mixture of penicillamine, hypotaurine, and epinephrine (PHE) solution in the in vitro fertilization (IVF) media seem to be a prerequisite when bovine spermatozoa are capacitated in vitro, in order to stimulate sperm motility and acrosome reaction. The present study was designed to determine the effect of the addition of heparin and PHE during IVF on the quality and penetrability of spermatozoa into bovine oocytes and on subsequent embryo development. Sperm quality, evaluated by the integrity of plasma and acrosomal membranes and mitochondrial function, was diminished (P < 0.05) in the presence of heparin and PHE. Oocyte penetration and normal pronuclear formation rates, as well as the percentage of zygotes presenting more than two pronuclei, was higher (P < 0.05) in the presence of heparin and PHE. No differences were observed in cleavage rates between treatment and control (P > 0.05). However, the developmental rate to the blastocyst stage was increased in the presence of heparin and PHE (P > 0.05). The quality of embryos that reached the blastocyst stage was evaluated by counting the inner cell mass (ICM) and trophectoderm (TE) cell numbers and total number of cells; the percentage of ICM and TE cells was unaffected (P > 0.05) in the presence of heparin and PHE (P < 0.05). In conclusion, this study demonstrated that while the supplementation of IVF media with heparin and PHE solution impairs spermatozoa quality, it plays an important role in sperm capacitation, improving pronuclear formation, and early embryonic development. © 2013 The Society for In Vitro Biology.
Keywords: Cattle; Embryo; Heparin; In vitro fertilization; PHE solution; Sperm membranes